[OP.7C.11] RELATIONSHIP BETWEEN DIMENSIONS OF THE ASCENDING AORTA AND CLINIC AND 24 HOURS BLOOD PRESSURE IN A GENERAL POPULATION IN NORTHERN ITALY. (September 2017) - Salvetti, M.; Paini, A.; Bertacchini, F.; Stassaldi, D.; Rosei, C. Agabiti; Aggiusti, C.; Rubagotti, G.; Maruelli, G.; Favro, S.; Rosei, E. Agabiti; Muiesan, M.L.
Abstract : Objective: Epidemiological studies have suggested that even mild enlargement of the ascending aorta may have independent prognostic significance for cardiovascular events. Therefore, some Authors have proposed that dilatation of the ascending aorta could be considered as a form of preclinical vascular damage in hypertensive patients. Aim of our study: was to assess the correlation between clinic and 24 hours BP values and the dimensions of the aorta, measured at level of the sinuses of Valsalva (Val), at the left ventricular outflow tract (LVOT), and at the level of the proximal ascending aorta (AscAO) in subjects from a general population. Design and method: 250 subjects (43% males, mean age 56 ± 4 years, 42% hypertensives-HT) underwent laboratory examinations, clinic and 24 hours BP measurement, cardiac and carotid ultrasound, carotid-femoral pulse wave velocity measurement (AoPWV). Results: Aortic diameters were greater HT as compared to NT (Val: 3.41 ± 0.54 vs 3.25 ± 0.41 cm, LVOT 2.10 ± 0.28 vs 2.04 ± 0.26, AscAo 3.39 ± 0.45 vs 3.18 ± 0.38, all p < 0.05). Aortic diameters were all correlated to clinic and 24 hours BP values. The coefficients of correlation were greater for 24 hours BP (Tab). Val, AscAo, LVOT were also significantly correlated with left ventricular mass (r = 0.61, r = 0.48, and r = 0.43, all p < 0.001), meanmax intima media thickness (r = 0.13, r = 0.24, and r = 0.13, all p < 0.05) and with AoPWV (r = 0.16, p < 0.05, r = 0.28 p < 0.001, r = 0.08 p = ns). Figure. No caption available. Conclusions: The dimensions of the proximal ascending aorta are significantly related to BP values in normotensive subjects and in hypertensive patients. Aortic dimension are more strictly related to twenty-four hours BP values than to clinic BP values. In this sample of general population a significant correlation between aortic dimensions and measures of cardiac and vascular organ damage was also observed, confirming the parallelism between different forms of organ damage